Hubungan Budaya Organisasi dengan Kinerja Perawat di Ruang Rawat Inap Rumah Sakit Daerah Liun Kendage Tahuna - Irma M. Yahya; Silvia Dewi Mayasari Riu; Aplisya Ester Datangmanis (Universitas Muhamadiyah Manado, 2024)
Organizational culture is a demand for every element of an organization to form attitudes and behaviors that are in accordance with the vision and mission. Nurse performance is one of the factors determining the success of a service in the hospital. The purpose of this study was to determine the relationship between organizational culture and nurse performance in the Inpatient Room of Liun Kendage Tahuna Hospital. This study is a quantitative study using a cross sectional approach. The sample was taken based on the number of respondents as many as 46 people using total sampling technique. The results of the analysis obtained a significant value of p = 0.009 less than the value (a) ≤0.05. The conclusion of this study is that there is a relationship between organizational culture and nurse performance in the Inpatient Room of Liun Kendage Hospital, Tahuna. It is expected to add insight for respondents about a strong organizational culture by increasing the level of education for nurses who have D3 graduates so that nurse performance will be better.